Linear and non-linear plasma equilibrium responses on the JT-60U and TCV tokamaks - Lister, J; Khayrutdinov, R; Limebeer, D; Lukash, V; Nakamura, Y; Sharma, A; Villone, F; Wainwright, J; Yoshino, R (2001)
Although linear response models are useful for feedback controller design, their linear time-invariant properties cannot simulate the evolution of a full plasma discharge. A suitable code for this purpose is DINA, which has now been benchmarked against a complete set of experimental data from TCV control experiments in both the time and frequency domains. Experimental measurements of the plasma equilibrium dynamic response to poloidal field coil voltage variations have recently been performed on the JT-60U tokamak. These results have been compared with the RZIP rigid current displacement model, previously validated on TCV, but enhanced for the work described. © 2001 Elsevier Science B.V. All rights reserved.